Pemberdayaan Masyarakat Desa Timang Gajah 2 melalui Pemanfaatan Lahan untuk Tanaman Obat Keluarga - Ernita Silviana; Amelia Sari; Burdah Ali; Nonong Hanis; Rima Hayati; Maria Irwani (Jurnal Abdimas Kesehatan (JAK), 2026)
This community service program aimed to empower the residents of Timang Gajah 2 Village, Gajah Putih Subdistrict, Bener Meriah Regency, to utilize home gardens through the cultivation of Family Medicinal Plants (TOGA). The activity was conducted on September 13, 2025, involving 15 participants. The method included interactive health education, leaflet distribution, hands-on TOGA planting practice, and the provision of TOGA seedlings for all participants. Evaluation was carried out using pretest and posttest questionnaires to measure knowledge improvement. The results showed an increase in the average knowledge score from 48% in the pretest to 78% in the posttest, as well as an increase in the “Good” knowledge category from 20% to 70%. These findings indicate that participatory education combined with practical demonstrations is effective in enhancing community understanding of home garden utilization for TOGA. This activity is expected to support community self-reliance in providing traditional medicine, encourage healthy lifestyles, and strengthen promotive and preventive health programs